Multicentre prospective observational study exploring the predictive value of functional echocardiographic indices for early identification of preterm neonates at risk of developing chronic pulmonary hypertension secondary to chronic neonatal lung disease. Issue 3 (31st March 2021) - Thomas, Laura; Baczynski, Michelle; Deshpande, Poorva; Kharrat, Ashraf; Joye, Sébastien; Zhu, Faith; Ibarra-Rios, Daniel; Shah, Prakesh S; Mertens, Luc; Jankov, Robert P; Ye, Xiang Y; Neary, Elaine; et al.
Abstract : Introduction: Although chronic pulmonary hypertension (cPH) secondary to chronic neonatal lung disease is associated with increased mortality and respiratory and neurodevelopmental morbidities, late diagnosis (typically ≥36 weeks postmenstrual age, PMA) and the use of qualitative echocardiographic diagnostic criterion (flat interventricular septum in systole) remain significant limitations in clinical care. Our objective in this study is to evaluate the utility of relevant quantitative echocardiographic indices to identify cPH in preterm neonates, early in postnatal course and to develop a diagnostic test based on the best combination of markers. Methods and analysis: In this ongoing international prospective multicentre observational diagnostic accuracy study, we aim to recruit 350 neonates born <27 weeks PMA and/or birth weight <1000 g and perform echocardiograms in the third week of age and at 32 weeks PMA (early diagnostic assessments, EDA) in addition to the standard diagnostic assessment (SDA) for cPH at 36 weeks PMA. Predefined echocardiographic markers under investigation will be measured at each EDA and examined to create a scoring system to identify neonates who subsequently meet the primary outcome of cPH/death at SDA. Diagnostic test characteristics will be defined for each EDA. Pulmonary artery acceleration time and tricuspid annular plane systolic excursion are the primary markers of interest. Ethics and dissemination: Ethics approval has been received by the Mount Sinai Hospital Research Ethics Board (REB) (#16-0111-E), Sunnybrook Health Sciences Centre REB (#228-2016), NHS Health Research Authority (IRAS 266498), University of Iowa Human Subjects Office/Institutional Review Board (201903736), Rotunda Hospital Research and Ethics Committee (REC-2019-008), and UBC Children's and Women's REB (H19-02738), and is under review at Boston Children's Hospital Institutional Review Board. Study results will be disseminated to participating families in lay format, presented to the scientific community at paediatric and critical care conferences and published in relevant peer-reviewed journals. Trail registration number: NCT04402645 .